Latin American &Amp; Caribbean Petroleum Engineering Conference 2007
DOI: 10.2118/107946-ms
|View full text |Cite
|
Sign up to set email alerts
|

Increase Heavy-Oil Production in Combustion Tube Experiments through the Use of Catalyst

Abstract: In this research a catalyst was evaluated in a combustion tube using heavy oil from Gulf of Mexico. The underlying objective is to increase the mobility of the oil inside the reservoir by effect of the catalyst during the combustion. The catalyst, used in the experiments was previously mixed with heavy crude oil of 12.5 °API. The catalyst, in liquid phase, is based in Molybdenum, Cobalt, Nickel and Iron. This organometallic catalyst is highly soluble and ultradispersed, and it was mixture wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Studies of catalytic low-temperature oxidation (CLTO) technologies applied on light oil at reservoir temperatures and pressures have seldom been reported in the published literature. The procedures and results of the previous studies , of crude oil catalytic oxidation technology are summarized in Table .…”
Section: Introductionmentioning
confidence: 99%
“…Studies of catalytic low-temperature oxidation (CLTO) technologies applied on light oil at reservoir temperatures and pressures have seldom been reported in the published literature. The procedures and results of the previous studies , of crude oil catalytic oxidation technology are summarized in Table .…”
Section: Introductionmentioning
confidence: 99%
“…Compared with metal oxide particles and water-soluble metallic salts, oil-dispersed metal-based catalysts started to be studied relatively late (see Table ). In 2007 and 2008, Ramírez-Garnica et al , reported Ni, Mo, Fe, and Co-based acetylacetonate or alkylhexanoate as oil-dispersed organometallic catalysts for increasing oil production in ISC processes. They indicated that these organometallic catalysts accelerated the combustion front propagation velocity, improved the combustion efficiency of oils, and increased oil recovery.…”
Section: Catalytic Oxidation Of Crude Oil Oxidationmentioning
confidence: 99%
“…Because of these unpleasant aspects of metals, metal oxides, and water-soluble metal salts as a catalyst or a precursor, ISC technology has tended to emphasize the need for other species of catalysts or precursors that are widely distributed and readily soluble in heavy oil continue . Using metal catalysts with a high valence electronic state and being oil-soluble or oil-dispersed in heavy crude oil in the ISC process dramatically improves stability of the combustion front. ,,, Recently, oil-soluble and oil-dispersed catalysts, due to their high distribution in the crude oil environments, have been considered as an option for oil oxidation in porous media to improve the enhanced oil recovery and reduced the viscosity of the produced oil. ,, Previous work by our group has shown that oil-dispersed iron oxide is highly distributed in heavy oil environments, including both liquid and porous forms, resulting in lower ignition temperatures and oxidation temperatures in both stages of heavy oil combustion (LTO and HTO) …”
Section: Introductionmentioning
confidence: 99%